Performance and Emission Characteristics of a Diesel Engine Fueled with Fish-Oil Biodiesel - B., Ghobadian; G., Najafi; R., Mamat; M. M., Noor; R., Yahyaee (2015)
The purpose of this study is to experimentally analyse the performance and the exhaust emissions of a diesel engine operating on fish oil-biodiesel blended fuels. The fish oil was separated from fish wastes with the help of the designed oil extraction machine. Biodiesel fuel was then produced from the extracted fish oil after the chemical reaction (transestrification, reaction between methanol, potassium hydroxide and oil from fish waste). Six cylinders, four-stroke diesel engine was fuelled with these new blended fuels (B0, B2.5, B5, B7.5 and B10) and operated at different engine speeds (800-1000 rpm). Experimental test results indicated the fact that blending fish oil biodiesel and diesel fuels, increased diesel engine performance variables including engine power and torque output. For diesel-biodiesel it was found that the brake specific fuel consumption (bsfc) was decreased compared to the net diesel fuel. The results showed that with increasing of biodiesel concentrations at diesel-biodiesel blended fuel, CO2 emissions increased, CO emission in a biodiesel-diesel fuel was lower significantly compared to pure diesel fuel. UHC emission with diesel-biodiesel blended fuel decreased. The trend of NOx emission was inverse compared to the UHC emission. With increasing of biodiesel concentration in blended fuels, NOx increased compared to the net diesel fuel. The tests revealed that fish oil biodiesel can be blended with diesel fuel to improve complete combustion of the fuel and reduce the exhaust emissions significantly.